Implementasi Metode Design Thinking Pada Perancangan UI/UX Design Aplikasi FinTrack - Rohmah, Putri Anjilis (JATISI, 2024)
Personal financial management is an important thing in life that is often a challenge for many people. The aim of this research is to design a mobile-based personal financial management application using the Design Thinking method. This method includes five main steps: Emphatize, Define, Ideate, create a prototype, and Testing. In the testing phase, Maze Design is used to evaluate the effectiveness and usability of the application. Test results show that the FinTrack application can provide an intuitive user experience and support their financial management. This research is expected to improve users' financial discipline, provide intuitive tools for personal financial management and provide an effective means for achieving financial stability.